2022
DOI: 10.3390/w14050708
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Center Pivot Irrigation to Regulate Field Microclimate and Wheat Physiology under Dry-Hot Wind Conditions in the North China Plain

Abstract: The dry-hot wind climate is one of the major agro-meteorological disasters associated with high temperature, low humidity, and specific wind forces, which seriously affects the yield of wheat in the North China Plain. A field experiment was conducted to investigate the field microclimate, net photosynthetic rate, chlorophyll content of flag leaves, grain filling rate, and wheat yield after sprinkler misting under the condition of a dry-hot wind climate in the 2018 and 2019 seasons. Two travel speeds, full and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, the positive impact of water spray on the temperature of the soil's upper layer and the canopy temperature has been proven in other research works [112]. Cai et al conducted a study on optimizing CPS to regulate field microclimate and reported improvement in the peak splits of temperature difference and photosynthesis rate [113]. Besides these optimistic impacts, there are some undesirable losses associated with sprinkler irrigation in terms of wind drift and evaporation.…”
Section: Sprinkler Design For Better Microclimate and Associated Fiel...mentioning
confidence: 92%
“…Moreover, the positive impact of water spray on the temperature of the soil's upper layer and the canopy temperature has been proven in other research works [112]. Cai et al conducted a study on optimizing CPS to regulate field microclimate and reported improvement in the peak splits of temperature difference and photosynthesis rate [113]. Besides these optimistic impacts, there are some undesirable losses associated with sprinkler irrigation in terms of wind drift and evaporation.…”
Section: Sprinkler Design For Better Microclimate and Associated Fiel...mentioning
confidence: 92%
“…affect plant growth, flowering, grain development and ultimately productivity of wheat crop (Zhang et al, 2023). The temperature plays a crucial role in determining the protein content of wheat and affects different stages of its growth (Cai et al, 2022;Wieser et al, 2023). The occurrence of hot wind poses a substantial agrometeorological hazard for wheat crops due to its potential to trigger a decline in humidity levels.…”
Section: Introductionmentioning
confidence: 99%